Improvement of student’s motivation to research activities in the process of studying - Berestova, Anna V.; Kolosov, Sergey V.; Tsvetkova, Milena I.; Grib, Elena V. (Opción)
In the article, the authors explore ways to increase students’ motivation for research activities in the process of studying based on a sociological survey. As a result, it is necessary to take into account the need to create a unified system of organizing research work in a university developed on the basis of a serious laboratory complex that would ensure the integration of education, science, and industry. In conclusion, universities today are faced with the intellectual passivity of students, unwillingness to learn, inability to independently acquire knowledge and find various ways to solve problems.